Pengaruh Latihan Isotonic Low Impact Pada Otot Dorsal Dan Plantar Flexor Terhadap Peningkatan Keseimbangan Dinamis Lansia - Farahnaz, Amzy, Sugiono Sst.Ft.,M.H. (Kes) (2016)
Background: The Elderly is advanced stage of life that is characterized by decreased ability of the body to adapt of the stressing in the environment and does not constitute a disease. Decrease the body's ability in elderly onset disturbances as potentially impaired balance. Because of the disruption that resulted in balance elderly so hampered the activities of its current status as the movement becomes sluggish, the difficulty of the move from sitting to standing, and walking, squatting and obstacles in doing daily activities such as can't walk away, while the defecate activities. Balance is the ability to pay attention to the balance of the body when placed at different positions either static or dynamic. Factors that play a role in disorders of balance the presence of intrinsic and extrinsic factors on the elderly.Isotonic exercise is a form dynamic exercise to fight a constant load or changed. Where there is a lengthening and shortening through a range of motion. Objective: This research aims to know the influence of muscle reinforcement dorsal and plantar flexor to the dynamic balance of the elderly. Results: After dorsal muscle strengthening exercises and plantar flexor 3 times a week for 4 weeks, the obtained results in increased muscle strength treatment group. Test for influence of isotonic exercise the granting of low impact towards the enhancement of dynamic balance of elderly obtained results that the significance value (p) = 0.007 or 0.007 < 0.05, then Ho denied existence of conclusions can be drawn so as to influence the awarding of isotonic exercise low impact towards the enhancement of dynamic balance elderly. Whereas in the control group values the significance of results obtained (p) = 1.000 or 1.000 > 0.05, then Ho accepted the conclusion can be drawn so that there is no influence on the control group. Conclusion: The giving of muscle reinforcement exercise dorsal and plantar flexor group treatment can increase the dynamic balance on the elderly. While there is no increase in the influence of dynamic balance in a control group not given the muscle strengthening exercise dorsal and plantar flexor.